Benefits of emotional inтelligence for retail - Mykilchenko, Maria Mykolayivna (Національний технічний університет "Харківський політехнічний інститут", 2020)
This article is devoted to the issue of emotional intelligence in the life of each person an in retail. The idea is based on the fact that the EQ itself has a decisive influence on the formation of the individual and his integration into the society. Also, the comparative characteristics of two types of intelligence and their importance in the development of personality, its development and success in retail. The author analyzes different types of thinking, the concept of emotions and the ways of their correction for mental and intellectual development, because emotions are the driving force in both personal life and the professional field. There is an opinion that without emotional intelligence it is now impossible to move forward or reach any significant heights, it can be developed and improved. Particular attention is paid to aspects of emotional intelligence and real steps that need to be taken to realize their own potential. Also the article reveals information about the ability to control our own emotions and our own understanding of our weaknesses and strengths. The article presents vivid examples of the real importance of EQ in business, management and retail. Provides practical recommendations for raising the level of emotional intelligence. The conclusion formed the main results of the study and analysis of EQ.

Дана стаття присвячена питанню емоційного інтелекту в житті кожної людини та в роздрібній торгівлі. Обґрунтовується ідея про те, що саме EQ – має вирішальний вплив на формування індивіду та його інтеграцію в соціум. Також в роботі надається порівняльна характеристика двох типів інтелекту та їх важливість у становленні особистості, її розвитку та успішності в сфері торгівлі. Автор аналізує різні типи мислення, поняття емоцій та шляхи їх корекції для ментального та інтелектуального розвитку, адже емоції є рушійною силою як в особистому житті, так і на професійному поприщі. Доводиться думка про те, що без емоційного інтелекту зараз неможливо рухатись вперед чи досягати якихось значних висот, його можна розвивати та вдосконалювати. Особливу увагу приділено аспектам емоційного інтелекту та реальним крокам, яких треба притримуватись для реалізації власного потенціалу. Також в статті розкривається інформація про вміння контролювати власні емоції та про власне розуміння своїх слабких та сильних сторін. В статті наведені яскраві приклади реальної важливості EQ в бізнесі, менеджменті та торгівлі. Надаються практичні рекомендації стосовно підвищення рівня емоційного інтелекту. У висновку сформовані основні результати дослідження та аналізу емоційного інтелекту та його ролі в житті кожного з нас.
Переваги емоційного інтелекту для роздрібної торгівлі
Keywords: emotions; styles of thinking; self-analysis; self-control; емоції; стилі мислення; самоаналіз; самоконтроль